2006
DOI: 10.1021/la0603774
|View full text |Cite
|
Sign up to set email alerts
|

Permeability and Electrokinetic Characterization of Poly(ethylene terephthalate) Capillary Pore Membranes with Grafted Temperature-Responsive Polymers

Abstract: Poly(ethylene terephthalate) (PET) track-etched membranes with average pore diameters of 692 and 1629 nm were functionalized using the monomer N-isopropylacrylamide (NIPAAm) and a photoinitiated "grafting-from" approach in which a surface-selective reaction has been most efficiently achieved by combinations of the unmodified PET surface with benzophenone and, alternatively, of an aminated PET surface with benzophenone carboxylic acid. Consistent estimations of the pore diameters of the base PET membranes and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
117
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(124 citation statements)
references
References 36 publications
7
117
0
Order By: Relevance
“…[61] For example, Ulbricht et al reported that functionalized membranes covered by a collapsed polymer hydrogel layer of several nanometers thick exhibit almost zero values of zeta potential. [26] The third possible way for the diminishing current rectification is the enlargement of the pore diameter due to the collapse of PNIPAM brushes. [53,62] This assumption can be justified by the parallel experiments conducted on another series of samples with larger tip diameter of~40 nm (see Supporting Information, Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…[61] For example, Ulbricht et al reported that functionalized membranes covered by a collapsed polymer hydrogel layer of several nanometers thick exhibit almost zero values of zeta potential. [26] The third possible way for the diminishing current rectification is the enlargement of the pore diameter due to the collapse of PNIPAM brushes. [53,62] This assumption can be justified by the parallel experiments conducted on another series of samples with larger tip diameter of~40 nm (see Supporting Information, Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…section 3.3.1) [10][11] and a thickness of 23 µm were purchased from Oxyphen GmbH (Dresden, Germany). Regenerated cellulose membranes (RC 60) with 75 m thickness, about 50 mm diameter, and 1.0 m average effective pore diameter were purchased from Whatman, Inc.…”
Section: Methodsmentioning
confidence: 99%
“…In comparison with the old product which has been used by Ulbricht and his coworkers, [10][11] the distribution of pore size has been extended but is still acceptable. The membrane morphology was further characterized by SEM.…”
Section: Characterizations Of Base Pet Membranementioning
confidence: 99%
“…PET track-etched membranes with nominal pore sizes of 400 nm and 1000 nm, respectively, were obtained from Oxyphen (Dresden, Germany); their pore diameters determined by permporometry were 692AE17 nm and 1629AE130 nm, respectively [13]. For oxidative hydrolysis ("carboxylation"), the unmodified PET membranes were immersed in a reaction mixture of 10 g KMnO 4 (Fluka, p.a.)…”
Section: Methodsmentioning
confidence: 99%